2020
DOI: 10.17305/bjbms.2019.4533
|View full text |Cite
|
Sign up to set email alerts
|

Circulating long noncoding RNAs H19 and GAS5 are associated with type 2 diabetes but not with diabetic retinopathy: A preliminary study

Abstract: Recently, a wide range of biological and pathological roles of long noncoding RNAs (lncRNAs) have been discovered. However, the potential role of circulating lncRNAs H19 and GAS5 in type 2 diabetes mellitus (T2DM) and diabetic retinopathy (DR) is not clear. Here, we assessed the plasma levels of H19 and GAS5 lncRNAs in T2DM patients with/without DR and evaluated if H19 and GAS5 pre-treatment plasma levels are a predictor of early response to a single aflibercept dose in DR subgroup. Plasma lncRNA expression pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Similarly, H19 was described as a significant prognostic marker in chronic liver disease patients with or without cirrhosis and HCC [105]. Consequently, as Fawzy et al [44] demonstrated in their study, H19 levels are significantly higher in plasma of T2D patients, though a receiver operating characteristics (ROC) analysis was not performed. Additionally, Tello-Flores et al [106] demonstrated in their study that the relative expression of serum H19 was two-fold higher among patients with impaired glycemic control when compared to diabetics with proper glucose control.…”
Section: Prognostic Potentialmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, H19 was described as a significant prognostic marker in chronic liver disease patients with or without cirrhosis and HCC [105]. Consequently, as Fawzy et al [44] demonstrated in their study, H19 levels are significantly higher in plasma of T2D patients, though a receiver operating characteristics (ROC) analysis was not performed. Additionally, Tello-Flores et al [106] demonstrated in their study that the relative expression of serum H19 was two-fold higher among patients with impaired glycemic control when compared to diabetics with proper glucose control.…”
Section: Prognostic Potentialmentioning
confidence: 93%
“…Conclusively, evidence presented by Liu et al further underlined the magnitude of H19's input in hepatic insulin resistance development because it affects not only gluconeogenesis but also hepatic lipogenesis. Recently, Fawzy et al [44] found that H19 circulating levels were significantly increased among patients with T2D, which indicates that it may serve as a blood-based marker of hepatic insulin resistance, especially since its dysregulation has been described in a variety of metabolic disorders.…”
Section: Long-non-coding Rna H19mentioning
confidence: 99%
“…LncRNA GAS5 (growth-arrest specific transcript 5) is known as a cancer-suppressor that regulates cell growth, survival, and proliferation and is also involved in cancer [ 176 ] and T2DM [ 177 ] aetiology. Recently, it was shown that GAS5 is involved in PCOS and the associated IR pathogenesis.…”
Section: Long Noncoding Rnas—new Regulators Of Pcos Inflammationmentioning
confidence: 99%
“…These include LINC00523, LINC00994, 200 LY86‐AS1, HCG27_201, 201 THRIL, and SALRNA1 192 . Moreover, studies showed that levels of GAS5 lncRNA were decreased both in serum and in plasma of patients with T2D 197,202 . Lastly, the lncRNA HI‐LNC45 was found downregulated in human T2D islets 198 …”
Section: Lncrnas In Obesity‐associated Diseasesmentioning
confidence: 99%
“…Interestingly, LncRNA‐p3134 is highly expressed in serum's exosomes of patients with T2D as studies found that it is secreted by islet β‐cell 196 . Moreover, the lncRNA H19 was found upregulated in plasma of patients with T2D, 197 and the lncRNA KCNQ1OT1 was upregulated in T2D islets 198 . Evidences can also be obtained from murine models of the disease, as is the case of E330013P06, which was found upregulated firstly in macrophages of diet‐induced insulin‐resistant T2D mice and subsequently also found upregulated in monocytes from patients with T2D 199 …”
Section: Lncrnas In Obesity‐associated Diseasesmentioning
confidence: 99%